Fixed‐ratio combination of insulin glargine plus lixisenatide (iGlarLixi) improves ß‐cell function in people with type 2 diabetes. Issue 6 (28th March 2022) - Ferrannini, Ele; Niemoeller, Elisabeth; Dex, Terry; Servera, Soraly; Mari, Andrea
Abstract: Aim: Multiple studies support the efficacy of combining a glucagon‐like peptide 1 receptor agonist (GLP‐1RA) with basal insulin in people with type 2 diabetes inadequately controlled on dual/triple oral therapy. Fixed‐ratio combinations of basal insulin + GLP‐1RA represent a further advance to facilitate management. We assessed the impact of fixed‐ratio combination basal insulin + GLP‐1RA treatment on β‐cell function. Materials and Methods: We analysed data from 351 participants in the LixiLan‐G trial (NCT02787551) randomized to receive iGlarLixi (insulin glargine 100 U/ml + lixisenatide) or to continue daily/weekly GLP‐1RA, both on top of metformin. Participants received a 2‐h meal tolerance test before randomization and at study end (26 weeks), with timed plasma glucose and C‐peptide determinations. β‐cell function parameters were resolved using mathematical modelling. Results: In the GLP‐1RA group (n = 162), both body weight and glycated haemoglobin decreased at week 26, yet none of the insulin secretion/β‐cell function parameters changed significantly. In contrast, in the iGlarLixi group (n = 189), glycated haemoglobin decreased significantly more than in the GLP‐1RA group ( p  < .0001) despite an increase in body weight (+1.7 ± 3.9 kg, p  < .0001). Fasting and stimulated insulin secretion decreased at Week 26 (both p  < .0001 vs. GLP‐1RA), while β‐cell glucose sensitivity increased by a median 35% ( p  = .0032 vs. GLP‐1RA). The incremental meal tolerance test glucose area showed a larger reduction with iGlarLixi versus GLP‐1RA ( p  < .0001). Conclusions: In people with type 2 diabetes on metformin, 26‐week treatment with iGlarLixi resulted in a marked improvement in β‐cell function concomitant with sparing of endogenous insulin release and a reduction in meal absorption.